Analysis of curriculum implementation in the accounting major at SMKN 11 Bandung - Anisa Latifah; Restu Setia Ningati; Nabil Abdillah Meyza Winata; Hafsah Nugraha (Hipkin Journal of Educational Research, 2025)
The educational curriculum determines the direction, goals, and learning strategies. Especially at the vocational education level, the curriculum is designed to produce graduates ready with competencies that suit the demands of the world of work. This research aims to analyze the implementation of Kurikulum Merdeka in accounting learning at SMKN 11 Bandung and its impact on student competence. Through this study, it is hoped that it can provide innovative solutions to overcome the challenges of implementing the Kurikulum Merdeka in other vocational schools. This research was conducted using a descriptive qualitative approach through interview, observation, and document analysis methods with the subject of an accounting teacher who also serves as a school curriculum staff. The results showed that Kurikulum Merdeka has been implemented effectively at all levels of learning. The implementation of this curriculum includes curriculum development based on synchronization with industry needs, innovative learning methods such as project-based learning, and evaluation that focuses on student competence. This research also emphasizes the importance of collaboration between teachers, students, parents, and industry in improving the relevance of the education curriculum.   Abstrak Kurikulum pendidikan memiliki peran yang cukup penting sebagai acuan dalam menentukan arah, tujuan, dan strategi pembelajaran. Khususnya pada jenjang pendidikan kejuruan, kurikulum dirancang untuk menghasilkan lulusan yang siap dengan kompetensi yang sesuai dengan tuntutan dunia kerja. Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Merdeka pada pembelajaran akuntansi di SMKN 11 Bandung serta dampaknya terhadap kompetensi peserta didik. Melalui studi ini, diharapkan dapat memberikan solusi inovatif guna mengatasi berbagai tantangan yang muncul dalam penerapan Kurikulum Merdeka di sekolah-sekolah kejuruan lainnya. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif deskriptif melalui metode wawancara, observasi, dan analisis dokumen dengan subjek seorang pendidik akuntansi yang juga bertugas sebagai staf kurikulum sekolah. Hasil penelitian menunjukkan bahwa Kurikulum Merdeka telah diterapkan di seluruh jenjang pembelajaran dengan tingkat efektivitas. Penerapan kurikulum ini mencakup pengembangan kurikulum berbasis sinkronisasi dengan kebutuhan industri, metode pembelajaran inovatif seperti project-based learning, serta evaluasi yang terfokus pada kompetensi peserta didik. Penelitian ini juga menegaskan pentingnya kolaborasi antara pendidik, peserta didik, orang tua, dan pihak industri dalam meningkatkan relevansi kurikulum pendidikan. Kata Kunci: implementasi kurikulum; Kurikulum Merdeka; pengembangan kurikulum